APPLICATION OF OPTIMAL CONTROL THEORY IN THE SPREAD OF SEXUAL HARASSMENT - Alberta Wijaya, Dania
Sexual harassment cases in Indonesia is increasing rapidly and the main cause is in the power imbalance between the victims and the perpetrators. However, based on the statement by Komnas Perempuan, this issue remains inadequately addressed although the fear of a harassment restricts the freedom and enjoyment of the people. There is a need to develop strategies to decrease the spread of sexual harassment by reducing both the number of victims and perpetrators. Potential strategies include providing safeguarding services for individuals at risk of sexual harassment, offering victim rehabilitation services, enforcing legal penalties for perpetrators, and conducting intensive efforts to catch offenders. The spread of sexual harassment can be represented into a mathematical model, while the four strategies can be represented as control variables that is applied to the model. An optimal control problem is formulated to address the impact of the strategies on the spread of sexual harassment using optimal control theory and solved with Pontryagin’s Minimum Principle (PMP). Simulation analyses from this study shows that without any strategies the number of victims and perpetrators respectively decreased by 0.5562% and 97.6138% in 100 days. Meanwhile, the most effective approach to reducing both victims and perpetrators involves the implementation of all four strategies simultaneously that results in the decrease of the number of victims by 99.9876% and perpetrators by 98.7771% in 100 days.